(untitled) (Third Sector Social Economic Review, 2025)
Many factors can influence consumers’ online food ordering intentions and their eating motivations. The current research aimed to examine these factors in terms of consumers’ smartphone addiction, life satisfaction, the perceived value of online food ordering, and online food ordering promotions. The design of this quantitative research consists of descriptive and correlational analysis methods. Within the scope of purposive sampling, data were collected from 305 university students who had previously ordered food online through an online survey form. Validity, reliability, direct and indirect effects were analyzed using partial least squares structural equation modeling. When the findings of the study are examined, it is found that consumers with intense smartphone addiction also have intense emotional and economic eating motivations, and intense emotional and economic eating motivations increase the utilization of promotions related to online food ordering. As consumers’ smartphone addiction increases, their economic eating motivations increase, and the increase in their economic eating motivations increase their perceived value of the intention to order food online. As consumers’ perceived value of online food ordering increases, their online food ordering intentions also increase. Consumers with health eating motivations have high life satisfaction. In addition, the mediating roles of emotional and economic eating motivations and perceived value were also identified in the study.